1999
DOI: 10.1164/ajrccm.160.5.9901093
|View full text |Cite
|
Sign up to set email alerts
|

Coughing in Laryngectomized Patients

Abstract: Ablation of the larynx implies withdrawal of afferent information from receptors involved both in the control of expiratory flow and in the genesis of protective airway reflexes including coughing. To investigate the effects of laryngectomy on the sensory and motor component of coughing, maximal voluntary cough (MVC) efforts as well as the reflex cough (RC) responses at threshold (T) and suprathreshold (1.8 x T, ST) levels induced by inhalation of progressively increasing concentrations of ultrasonically nebul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 20 publications
4
53
0
1
Order By: Relevance
“…The inductance vest is probably inaccurate during the vigorous movements of the torso in coughing; however, cough expiratory flow and volume during voluntary or induced cough efforts can be measured fairly accurately using a calibrated pneumotachograph [17]. Since the force developed during the expulsions of cough largely depends upon the magnitude of the preceding inspiration [11], measurements of cough inspiratory volume might also represent a useful indicator of cough intensity.…”
Section: Both Methods Have Advantages and Disadvantagesmentioning
confidence: 99%
See 2 more Smart Citations
“…The inductance vest is probably inaccurate during the vigorous movements of the torso in coughing; however, cough expiratory flow and volume during voluntary or induced cough efforts can be measured fairly accurately using a calibrated pneumotachograph [17]. Since the force developed during the expulsions of cough largely depends upon the magnitude of the preceding inspiration [11], measurements of cough inspiratory volume might also represent a useful indicator of cough intensity.…”
Section: Both Methods Have Advantages and Disadvantagesmentioning
confidence: 99%
“…Since the magnitude of EMG activity correlates with the force produced by the contracting muscle [31], recordings of EMG activity of human abdominal muscle activity have been used to assess the intensity of induced cough efforts [see 32, and for further refs]. In particular, the 'moving average' integrated EMG activity of the obliquus externus muscle, perhaps the principal muscle implicated in the production of cough force, has been used to evaluate the intensity of voluntary and reflex cough efforts in humans [11,17].…”
Section: Muscular Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Lasserson et al [10] showed a much higher activation of 79.7±41.6% following tartaric acid inhalation. Normalizing peak EMG activity for EO produced a 50% increase in cats with mechanical stimulation of the larynx [23] and 78-83% in humans using fog [5,17,19]. In addition to method of analysis, the type of tussive agent used and the species of the test subject will also add variability to the data.…”
Section: Motor Neural Activationmentioning
confidence: 99%
“…With this technique, capsaicin concentrations (or other tussives such as citric acid and distilled water) are doubled until two and five "cough events" (typically defined by the number of expulsive events, or "cough sounds") are achieved, representing the threshold and suprathreshold response, respectively. These studies have shown differences in the cough response between ages [13], genders [14][15][16] and diseases [4,5,13,17]. However, these data cannot infer changes in expiratory muscle activation, duration of expulsive phases and the airflow dynamics with increasing capsaicin concentration, all which are essential components in defining the cough response.…”
Section: Introductionmentioning
confidence: 99%